2021
DOI: 10.3390/ijms22179124
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Binding Mechanism of PF-07321332 SARS-CoV-2 Protease Inhibitor through Molecular Dynamics and Binding Free Energy Simulations

Abstract: The novel coronavirus disease, caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), rapidly spreading around the world, poses a major threat to the global public health. Herein, we demonstrated the binding mechanism of PF-07321332, α-ketoamide, lopinavir, and ritonavir to the coronavirus 3-chymotrypsin-like-protease (3CLpro) by means of docking and molecular dynamic (MD) simulations. The analysis of MD trajectories of 3CLpro with PF-07321332, α-ketoamide, lopinavir, and ritonavir revealed that 3CLpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 52 publications
(66 reference statements)
3
76
0
1
Order By: Relevance
“…This demonstrated that all three compounds effectively occupy the catalytic dyad of the Mpro and prevent its substrate from binding to the Mpro. A recent study showed that PF-07321332 and α-ketoamide performed better than Lopinavir and Ritonavir, due to their ability to disrupt the catalytic dyad residue His41-Cys145 of Mpro [ 53 ]. These three compounds disrupt the catalytic dyad by interacting with His41-Cys145, which is similar to PF-07321332 and α-ketoamide.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated that all three compounds effectively occupy the catalytic dyad of the Mpro and prevent its substrate from binding to the Mpro. A recent study showed that PF-07321332 and α-ketoamide performed better than Lopinavir and Ritonavir, due to their ability to disrupt the catalytic dyad residue His41-Cys145 of Mpro [ 53 ]. These three compounds disrupt the catalytic dyad by interacting with His41-Cys145, which is similar to PF-07321332 and α-ketoamide.…”
Section: Resultsmentioning
confidence: 99%
“…To date, remdesivir has been approved by the U.S. Food and Drug Administration (FDA), but it is not recommended by the World Health Organization due to insufficient evidence of its effectiveness against COVID-19. The mutagenic ribonucleoside molnupiravir [ 53 ] and the 3CLpro inhibitor nirmatrelvir/PF-07321332 (Paxlovid ® ) [ 54 ] are two recently FDA-approved oral antivirals for the treatment of COVID-19. However, there are some safety concerns regarding molnupiravir, as it can cause mutations in host cells [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…To examine the binding mode of the novel PLpro inhibitors, authors obtained co-crystal structures of XR8-24, XR8-65, XR8-69, XR8-83, and XR8-89 with SARS-CoV-2 PLpro (PDB: 7LBR, 7LBS, 7LLF, 7LLZ, and 7LOS) (Table 1). Superposition of the ligand-bound structures shows all inhibitors utilized the same binding mode similar to GRL0617, including closure of BL loop and H bond between amide of inhibitor and D164 and Q269 (Osipiuk et al, 2021a;Gao et al, 2021;Ratia et al, 2008;Ahmad et al, 2021). The analysis of the representative cocrystal structures of XR8-24 and XR8-89 found that the azetidine ring extends into Site I to interact with side chain of E168 (Figures 5B,C) (Shen et al, 2021).…”
Section: Development Of Grl0617 Derivativesmentioning
confidence: 95%